Schoenberg: Pierrot Lunaire - Dunsby, Jonathan (Cambridge Cambridge University Press, 1992)
Pierrot lunaire (1912) is one of the most important music theater works ever written. This is the first guide in English to a work that continues to be performed, broadcast, and recorded worldwide. The book describes the artistic environment around the turn of the century from which Pierrot emerged, and discusses Schoenberg's working methods and intentions in composition. In a clear and imaginative description of the work itself, the author takes each of the twenty.